Upaya KPPU Menangani Dugaan Pelanggaran Layanan Rapid Test Diagnosis Covid-19 - Izzah Khalif Raihan Abidin (Faculty of Law, Universitas Airlangga, 2021)
AbstractIndonesian Competition Commission (KPPU) conducted an initiative case research to the alleged tying-in Rapid Test services agreement in several hospitals. In the research, all hospitals that offer Rapid Test services are the objects of research. KPPU conducts market structure analysis, compliance with the elements of Article 15 paragraph (2) of Law No. 5 of 1999 on Prohibition of Monopolistic Practices and Unfair Competition, and the consequences of implementing closed agreements. Implementing this tying agreement may fall into the investigation category if, in practice, it causes monopolistic practices and or unfair business competition. Analyzing the KPPU's efforts to handle suspected business competition violations committed by hospitals, legal research will use a statutory and conceptual approach. Considering that the tying agreement can actually or potentially hinder business competition, based on KPPU's duties and authorities can enforce the law and advocate for business competition.Keywords: Tying Agreement; Rapid Test; Hospital; KPPU.AbstrakKomisi Pengawas Persaingan Usaha (KPPU) melakukan penelitian perkara inisiatif terhadap dugaan adanya perjanjian tying yang dilakukan sejumlah rumah sakit pada layanan Rapid Test. Dalam penelitian tersebut, seluruh rumah sakit yang menawarkan layanan Rapid Test menjadi objek penelitian, KPPU melakukan analisis struktur pasar, pemenuhan unsur-unsur Pasal 15 ayat (2) Undang-Undang No. 5 Tahun 1999 tentang Larangan Praktek Monopoli dan Persainan Usaha Tidak Sehat, dan akibat pelaksanaan perjanjian tertutup. Pelaksanaan perjanjian tying ini dapat masuk kategori penyelidikan jika dalam praktiknya menyebabkan praktik monopoli dan atau persaingan usaha tidak sehat. Dalam menganalisis upaya KPPU menangani dugaan pelanggaran persaingan usaha yang dilakukan rumah sakit, digunakan penelitian hukum melalui pendekatan peraturan perundang-undangan dan konseptual. Mengingat perjanjian tying secara aktual maupun potensial dapat menghambat persaingan usaha, maka KPPU berdasarkan tugas dan wewenangnya dapat melakukan penegakan hukum maupun advokasi persaingan usaha.Kata Kunci: Perjanjian Tying; Rapid Test; Rumah Sakit; KPPU.